Fas-ligand and caspase-3 positivity in three cases of histiocytic sarcoma: a different etiopathogenic pathway? - Cristiano Claudino Oliveira; Rafael Bispo Paschoalini; Maria Aparecida Custódio Domingues (University of São Paulo, 2018)
Histiocytic sarcoma (HS) is a rare malignant neoplasia of hematopoietic origin and unknown etiology. We studied three patients with histiocytic sarcoma reviewing the morphological and immunohistochemical aspects. We evaluated in particular, if apoptosis may be unbalanced in this disease. All cases have morphological and immunohistochemical features consistent with the diagnosis of histiocytic sarcoma. The markers CD163, CD68, vimentin, lysozyme, and S-100 were positive in all cases. Similarly, the three samples were positive for Fas-ligand and Caspase-3. It is well-known that neoplasms may induce increased levels of Fas-ligand with the blockade of the apoptosis process. In the context of HS, the increased Fas-ligand expression represents a new area for research. Indeed, it is linked to proinflammatory stimulus and, maybe with the association of an infection.